Perancangan Runing Teks Sebagai Media Publikasi Di Kantor Desa Menceh - Akbar, Taufik; Fathurrahman, Imam; Maulidi, Dedi; Haris, M.Sabirin; Pranata, Aditya; Sholihah, Hikmatun; Mu'Tashim, Aan (Jurnal Teknologi Informasi untuk Masyarakat, 2024)
The development of information and communication technology currently plays a very important role in various aspects of life, including village government. The use of computerized technology and information systems can increase efficiency, accuracy and transparency in public services. The Menceh Village Office is a place where village residents can gather to carry out various village activities or events, such as socialization held by the village government, village meetings, managing correspondence, and other administrative activities. Apart from that, the Village Office also functions as a place that provides information for village residents. To complete the facilities there, we from the SDGs-Based Village Development KKN, Faculty of Engineering, Hamzanwadi University took the initiative to create running text that can be used to display information or announcements. Previously the Village Office did not have an information board. With running text to display important information at the Village Office, it is hoped that it will be able to help village residents in obtaining important information and announcements from the Menceh Village government.